Risk Related to Pre–Diabetes Mellitus and Diabetes Mellitus in Heart Failure With Reduced Ejection Fraction: Insights From Prospective Comparison of ARNI With ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure Trial. (January 2016) - Kristensen, Søren L.; Preiss, David; Jhund, Pardeep S.; Squire, Iain; Cardoso, José Silva; Merkely, Bela; Martinez, Felipe; Starling, Randall C.; Desai, Akshay S.; Lefkowitz, Martin P.; Rizkala, Adel R.; Rouleau, Jean L.; et al.
Abstract : Background—: The prevalence of pre–diabetes mellitus and its consequences in patients with heart failure and reduced ejection fraction are not known. We investigated these in the Prospective Comparison of ARNI With ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure (PARADIGM-HF) trial. Methods and Results—: We examined clinical outcomes in 8399 patients with heart failure and reduced ejection fraction according to history of diabetes mellitus and glycemic status (baseline hemoglobin A1c [HbA1c]: <6.0% [<42 mmol/mol], 6.0%–6.4% [42–47 mmol/mol; pre–diabetes mellitus], and ≥6.5% [≥48 mmol/mol; diabetes mellitus]), in Cox regression models adjusted for known predictors of poor outcome. Patients with a history of diabetes mellitus (n=2907 [35%]) had a higher risk of the primary composite outcome of heart failure hospitalization or cardiovascular mortality compared with those without a history of diabetes mellitus: adjusted hazard ratio, 1.38; 95% confidence interval, 1.25 to 1.52; P <0.001. HbA1c measurement showed that an additional 1106 (13% of total) patients had undiagnosed diabetes mellitus and 2103 (25%) had pre–diabetes mellitus. The hazard ratio for patients with undiagnosed diabetes mellitus (HbA1c, >6.5%) and known diabetes mellitus compared with those with HbA1c<6.0% was 1.39 (1.17–1.64); P <0.001 and 1.64 (1.43–1.87); P <0.001, respectively. Patients with pre–diabetes mellitus were also at higher risk (hazard ratio, 1.27 [1.10–1.47]; P <0.001) compared with those with HbA1c<6.0%. The benefit of LCZ696 (sacubitril/valsartan) compared with enalapril was consistent across the range of HbA1c in the trial. Conclusions—: In patients with heart failure and reduced ejection fraction, dysglycemia is common and pre–diabetes mellitus is associated with a higher risk of adverse cardiovascular outcomes (compared with patients with no diabetes mellitus and HbA1c <6.0%). LCZ696 was beneficial compared with enalapril, irrespective of glycemic status. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01035255.